Tie-Dye Batik Training as a Medium for Creativity, Entrepreneurship, and Islamic Sciences Tramping for Students at Al-Intishor Islamic Boarding School - Teguh Ardianto; Syamsuddin, Syamsuddin; Rahmatun Inayah; Kormil Saputra; Ika Umratul Asni Aminy; Indrawan Eka Badri; Nurmutyah Naylah; Nur Azzahra Al Radiyah; Nurjannah, Nurjannah; Fauziana Hidayat; Sofiana Aprilia (Future Tecno-Science Publisher, 2025)
Batik is an Indonesian cultural heritage that embodies deep philosophical values and national identity. However, traditional batik-making techniques are often considered complex for beginners since they require specific skills. Therefore, the tie-dye technique, also known as batik ikat celup, is introduced as a simpler and more accessible alternative that can serve both as a learning medium and as an entrepreneurial opportunity. This community service program was conducted at Pondok Pesantren Al-Intishor, Mataram, involving 9th and 10th grade students. The method included delivering introductory materials, demonstrations, and hands-on practice in small groups under intensive guidance. The results revealed high enthusiasm among both students and teachers, who acknowledged the relevance of this activity to be integrated into craft and entrepreneurship education. Students successfully understood the stages of tie-dye batik making—from material preparation to the drying process—while also developing creativity through unique motifs and color variations. This program proved effective not only in enhancing knowledge about batik but also in fostering practical skills, self-confidence, and basic entrepreneurial potential. Thus, tie-dye batik training can be regarded as a strategic medium to preserve cultural heritage while simultaneously improving participants’ economic independence.